Enzalutamide alleviates anxiety and depression as well as improves quality of life compared to bicalutamide in metastatic castration-resistant prostate cancer patients: a cohort study - Guo, Feng; Li, Guo-Hao (Translational Cancer Research; Vol 8, No 5 (September 30, 2019): Translational Cancer Research, 2019)
Background: This study aimed to evaluate the efficacy of enzalutamide compared with bicalutamide on anxiety, depression and quality of life (QoL) in metastatic castration-resistant prostate cancer (mCRPC) patients. Methods: Totally 134 mCRPC patients were consecutively enrolled and baseline data were documented, among whom 53 patients received enzalutamide as Enzalutamide group, while 81 patients received bicalutamide as Bicalutamide group. Anxiety and depression were assessed by Hospital Anxiety and Depression Scale (HADS) as well as Zung Self-Rating Anxiety/Depression Scale (SAS/SDS), and QoL was assessed by Functional Assessment of Cancer Therapy (FACT)-General/Prostate (FACT-G/FACT-P) questionnaires at W0 (baseline), W12, W24, W36, W48 and W60. Results: No difference of HADS-anxiety (HADS-A), SAS, HADS-depression (HADS-D), SDS, FACT-G or FACT-P score at baseline was observed between Enzalutamide group and Bicalutamide group. Both HADS-A score and SAS score were decreased at W48 and W60 in Enzalutamide group compared to Bicalutamide group. HADS-D score was reduced at W60 and SDS score was attenuated at W48 and W60 in Enzalutamide group compared to Bicalutamide group. As to QoL assessments, FACT-G score disclosed no difference at each visit between Enzalutamide group and Bicalutamide group, while FACT-P score was decreased at W60 in Enzalutamide group compared to Bicalutamide group. In addition, the reduction of HADS-A, SAS, HADS-D, SDS, FACT-G and FACT-P scores from W0 to W60 were all higher in in Enzalutamide group compared to Bicalutamide group. Conclusions: In conclusion, enzalutamide presents with better efficacy on alleviating anxiety and depression, as well as improving QoL in mCRPC patients compared to bicalutamide.